Coloristic Style in the Works of Mo Yan in Chinese Romanticism - Shakhnoza Bakhtiyorovna , Muhamedjanova (International Journal of Psychosocial Rehabilitation, 2020)
The article is about the literary features of the Mo Yan novels, in which the element of colors in the work and the style of language are mentioned. Mo Yan novels are very important in the history of modern Chinese literature due to their style and language characteristics. At the same time, it had a great influence on the development of folk literature. The language style of the Mo Yan novels is unique and colorful; some of them are enriched with poetry, while others are narrative. Mo Yan novels have a very colorful interpretation. His thoughts, which he wants to say, are relatively simple and objective. This is one of the factors that distinguishes him from other authors and is the basis for the study of his works. The study of the literary features of Mo Yan novels is now of great importance in modern Chinese literature. Mo Yan looks for an independent and ideal human soul. He wants the peasants to live a free life and be free, and at the same time deeply criticizes the evil forces. In Mo Yan novels, color symbols are recognized in the flames.